Rancang Bangun Sistem Informasi TPU (Tempat Pemakaman Umum) Berbasis Web (Studi Kasus : TPU Desa Warungjeruk) - Muhammad Andi Rasyiddin; Susanna Dwi Yulianti Kusuma (CV. Multi Kreasi Media, 2023)
In this study, the researcher used the waterfall method, the waterfall method or model, which is the most widely used model for the development stage. This waterfall model is also known as the traditional model or classical model. The waterfall model is often also called the linear sequential model or the classic cycle. This waterfall model provides a sequential software lifeflow approach starting from the analysis, design, coding, testing and support stages.